IN VITRO STUDY ON NIGELLA SATIVA AS INHIBITOR OF CALCIUM OXALATE CRYSTALLIZATION (Indonesian Urological Association, 2022)
Objective: This study aims to test the efficacy of Nigella Sativa plant as an inhibitor of calcium oxalate crystallization. Material & Methods: Nigella Sativa alcohol extract was made by maceration of 100 grams Nigella seeds which were dried and powdered for 72 hours and then filtered, so as to produce 100 percent Nigella alcohol extract. Then make dilutions of 10 and 50 percent. The precipitation of calcium oxalate at 37 0C and pH 5.7 was studied by measurement of turbidity at 620 nm with and without inhibitor which is Nigella Sativa. Results: Tmax, the slope of nucleation (SN) and slope of aggregation (SA) was measured with control and with inhibitor. With increasing concentration of inhibitor, Tmax progressively increased, whereas SN and SA decreased. The nucleation percentage inhibition ratio was 86.0% and inhibition of crystal aggregation took place by 66.6% with 100% extract. Crystallization was inhibited (growth and aggregation) in a concentration dependent manner. Conclusion: Nigella Sativa is strong inhibitor of calcium oxalate crystallization. However, comprehensive work is needed to establish the results.